An Improved Scene Adaptive PRM Path Planning Algorithm - YANG Jingzhao, WANG Chao, ZHANG Yu (Zhihui kongzhi yu fangzhen)
Aiming at the contradiction between fineness, dynamics and planning real-time when planning ground unmanned equipment paths in dynamic and complex environments, a ground unmanned equipment path planning algorithm based on risk fusion cost map and adaptive PRM is proposed. Firstly, the risk fusion cost map is established based on the multi-factor environment scene, the scene adaptive PRM probabilistic road map is constructed through the mechanisms of Gaussian convolution adaptive sampling, nonlinear probability enhancement and secondary sampling strategy, and the local planner is utilized to dynamically update the weights of the probabilistic road map, so as to realize the optimized search of global low-risk cost paths. Simulation results show that the method can better realize the balance of fineness, dynamics and real-time planning in dynamic and complex environments.